2010
DOI: 10.1021/nn1018279
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors of NIH-3T3 Fibroblasts on Graphene/Carbon Nanotubes: Proliferation, Focal Adhesion, and Gene Transfection Studies

Abstract: Carbon-based materials, including graphene and carbon nanotubes, have been considered attractive candidates for biomedical applications such as scaffolds in tissue engineering, substrates for stem cell differentiation, and components of implant devices. Despite the potential biomedical applications of these materials, only limited information is available regarding the cellular events, including cell viability, adhesion, and spreading, that occur when mammalian cells interface with carbon-based nanomaterials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
269
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(288 citation statements)
references
References 46 publications
(70 reference statements)
15
269
0
Order By: Relevance
“…11−14 For instance, Ryoo et al showed that graphene substrates improved gene transfection efficacy in NIH-3T3 fibroblasts without inducing notable deleterious effects. 14 Chang et al found that graphene oxide (GO) did not enter A549 cells and showed no obvious toxicity to A549 cells. 15 On the contrary, Wang et al demonstrated that water-soluble GO had obvious toxicity to human fibroblast cells, such as decreasing cell adhesion, inducing cell apoptosis, and entering into lysosomes, mitochondria, endoplasm, and cell nucleus when the dose was higher than 50 μg/mL.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11−14 For instance, Ryoo et al showed that graphene substrates improved gene transfection efficacy in NIH-3T3 fibroblasts without inducing notable deleterious effects. 14 Chang et al found that graphene oxide (GO) did not enter A549 cells and showed no obvious toxicity to A549 cells. 15 On the contrary, Wang et al demonstrated that water-soluble GO had obvious toxicity to human fibroblast cells, such as decreasing cell adhesion, inducing cell apoptosis, and entering into lysosomes, mitochondria, endoplasm, and cell nucleus when the dose was higher than 50 μg/mL.…”
Section: ■ Introductionmentioning
confidence: 99%
“…NIH-3T3 fibroblasts behaviour was studied in different substrates covered with carbon nanomaterial, for example, GO, carbon nanotubes and RGO. The substrates coated with carbon nanomaterial had enhanced gene transfection efficiency and high biocompatibility [99]. Graphene/chitosan films demonstrated promising application to enhance and repair tissue functions in tissue engineering [100].…”
Section: Scaffolds For Mammalian Cell Culturementioning
confidence: 99%
“…In a 2015 report by Wan and colleagues, 19 researchers used quantitative Polymerase Chain Reaction (qPCR) -a very common molecular method -to newly identify NIH/3T3 (ATCC No. : CRL-1658) murine embryonic fibroblast cells as female; 3T3 cells have long been used in toxicological experiments, most recently to assess developmental toxicity to therapeutic drugs 20 and phototoxic potential, 21 but also to document cell behavior on nanotubes, 22 response to nanoparticles, 23 and antioxidant response. 24 Importantly, sex determination using qPCR is now added to the list of several other available tools that can be used to determine the sex type of cultured cells, including immunodetection of H-Y antigen, 25 nested PCR, 26 Southern blot, 27 and enzymatic assays.…”
Section: 18mentioning
confidence: 99%